The Pattern of Supervision and Action Against Illegal Financial Technology Peer to Peer Lending - Debora Debora; Haposan Siallagan (Magister of Law, Faculty of Law, University of Mataram, 2021)
The existence of illegal fintech is still a public concern due to the inadequate regulation tools that are able to regulate and take firm action against the existence of illegal fintech. The difficulty faced by regulators in taking action against illegal fintech is because it is difficult to be tracked and illegal entities that have been blocked can easily recreate new illegal fintech entities. This study was conducted by using normative legal research, which was reviewing material law that contains normative legal rules. As the result, there are conclusion namely, first Illegal fintech P2PL actors try to trick the public by resembling the company’s platform name and/or logo, name, and identity color from legal fintech P2PL that has been registered/licensed at the OJK and SWI’s efforts to take action against these fintech P2PL companies are by blocking sites, conducting joint inspections of business activities which assumed as illegal investments, ordering illegal fintech P2PL companies to stop business activities, and improving coordination in handling cases with related agencies. OJK through SWI seeks to stop the chain of Illegal fintech P2PL by routinely coordinating with the Minister of Communication and Information to block illegal services